Make it too difficult, and I'll give up; let me succeed, and I'll excel: The interaction between assigned and personal goals. (24th February 2020) - Fan, James; Gómez‐Miñambres, Joaquín; Smithers, Samuel
Abstract : We examine the motivational effects of setting both assigned and personal nonbinding goals on a real‐effort laboratory experiment. In order to derive conjectures for our experiment, we develop a model with goal‐dependent preferences. In line with previous studies, we find that goal setting leads to a higher performance. We also find that goal setting is most effective if subjects were able to achieve previous goals. Therefore, in goal setting, "success breeds success." In particular, we observe that when subjects are initially allowed to attain assigned goals, they are better at self‐motivating in the future when performing under personal goals.